Ichthyofaunal diversity of the major Indian rivers: A review - Das, Basanta K.; Bhakta, Dibakar; Kumar, Lohith; Nair, Sangeetha M.; Koushlesh, Satish K.; M., Sajina A.; M., Roshith C.; Samanta, S. (Journal of the Inland Fisheries Society of India, 2021)
t In the present communication, an attempt has been made to review the ichthyofaunal diversity of the important Indian rivers such as Ganga, Brahmaputra, Mahanadi, Godavari, Krishna, Cauvery, Tapti, Narmada, Yamuna, etc. Secondary data in the form of research articles, technical reports, technical bulletins, books, etc., were reviewed, bulk of which were published by ICAR-CIFRI and a few other institutions. Among these rivers, the fish diversity of the Yamuna, the Gandak, the Kathajodi, and the Tons (Tamas) have been studied for the first time by ICAR-CIFRI. River Ganga was the most frequently studied river while the ichthyofaunal studies of the river Tapti was done in a gap of over 50 years. Similarly, the entire stretch of the river Cauvery was studied after a gap of 28 years. The study highlights the need to explore fish fauna of the whole stretches of the major rivers of India at regular intervals to build a comparable database that might be utilized by the stakeholders for research, planning and management activities. Key words Fish biodiversity, Ganga, Mahanadi, Godavari, Krishna, Cauvery